2009
DOI: 10.1155/2010/934708
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Quality of Underground Water at Eloor in Ernakulum District of Kerala, India

Abstract: The physical and chemical properties of groundwater in Eloor, an industrial region, have been investigated to evaluate the extent of pollution. The study area was divided into four zones and a total of 40 water samples from different locations were collected, analyzed and correlation analysis has been carried out among the measured parameters. A comparison of the observed parameters with the limits prescribed by BIS revealed that in some area pH values are lower than the prescribed limit. The concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The cause of alkalinity is the minerals which dissolve in water from soil. Low value of alkalinity in the study area is indicative of low pH value (Tables 2 and 3) which agrees with Umadevi et al (2010).…”
Section: Total Alkalinity (Alk)supporting
confidence: 85%
“…The cause of alkalinity is the minerals which dissolve in water from soil. Low value of alkalinity in the study area is indicative of low pH value (Tables 2 and 3) which agrees with Umadevi et al (2010).…”
Section: Total Alkalinity (Alk)supporting
confidence: 85%
“…Mean values of the sampled wells in rural land use shows that, TDS and SO 4 concentration were within the WHO limit of 500mg/L while in urban land use, mean concentration of TDS (614.86mg/L) exceeds the WHO limit for drinking water. High concentration of sulfate along with magnesium in drinking water can lead to gastrointestinal irritation and respiratory illness [26].…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that the sources of chloride in water were mainly through industrial waste discharges and domestic wastes etc. 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Sulphate: Table 1 shows that the mean levels of sulphate in the borehole and sachet water samples were 20.12 and 13.90mg/l respectively. Research has shown that anthropogenic activities such as fertilizer application, pesticides and industrial effluent discharges are main sources of sulphate to water bodies 25 . The levels of sulphate in the water samples met the recommended permissible limits for a safe drinking water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation